A FARM SITE DEVELOPMENT METHOD: CREATING A ROADMAP TOWARDS SITE SATURATION - vd Merwe, Rone; Liebenberg, Andre; de Vries, Marne (The South African Journal of Industrial Engineering, 2014)
Agricultural engineering applies existing knowledge to provide for humanity’s greatest need: food for survival. This article presents an opportunity to augment existing agricultural engineering practices with industrial engineering techniques, with the aim of encouraging financial control during the expansion of assets on farms. Facility planning techniques are combined with a well-known enterprise engineering technique, the transformation roadmap, to develop a Farm Site Development Method (FSDM). The purpose of the FSDM is to provide method guidance in developing a facilities master plan to evolve farm facilities in a phased approach towards a future/saturation state. The article also presents an evaluation of the FSDM, via a practical demonstration at Waterfall Farm.